2017
DOI: 10.3892/br.2017.845
|View full text |Cite
|
Sign up to set email alerts
|

Cell culture density affects the stemness gene expression of adipose tissue-derived mesenchymal stem cells

Abstract: Abstract.The results of clinical trials using mesenchymal stem cells (MSCs) are controversial due to the heterogeneity of human MSCs and differences in culture conditions. In this regard, it is important to identify gene expression patterns according to culture conditions, and to determine how the cells are expanded and when they should be clinically used. In the current study, stemness gene expression was investigated in adipose tissue-derived MSCs (AT-MSCs) harvested following culture at different densities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 39 publications
(48 reference statements)
4
33
0
Order By: Relevance
“…However, after 10 days, the cells were hyperconfluent in both cases. Consequently, the expression of almost all genes decreased [42][43][44]. Nonetheless, the cells on the MCs performed well and their gene expression pattern was similar to that of those obtained from hASCs grown in static 2D conditions.…”
Section: Monitoring the Expression Of Selected Stemness Or Cell Diffesupporting
confidence: 63%
See 3 more Smart Citations
“…However, after 10 days, the cells were hyperconfluent in both cases. Consequently, the expression of almost all genes decreased [42][43][44]. Nonetheless, the cells on the MCs performed well and their gene expression pattern was similar to that of those obtained from hASCs grown in static 2D conditions.…”
Section: Monitoring the Expression Of Selected Stemness Or Cell Diffesupporting
confidence: 63%
“…The differences in the gene expression profiles were more pronounced on day 5. However, on day 10, due to the very high cell density, most of the stemness genes decreased and most of the differentiation genes increased in both systems, resulting in similar profiles [42][43][44]. These results clearly demonstrated that for both donors, the optimum point of harvest was on day 5-6 (see Section 3.3).…”
Section: Monitoring the Expression Of Selected Stemness Or Cell Diffementioning
confidence: 60%
See 2 more Smart Citations
“…A microarray study that systematically compared gene expression profiles of ASCs showed that proliferation-related genes were upregulated in cultures at ~50% confluence, whereas immunity and defense, cell communication, signal transduction, and cell motility genes were more highly expressed in cultures at ~90% confluence 30 . Moreover, stemness markers Nanog and c-Myc were altered in ASCs according to various seeding densities 31 . Sukho et al also reported that ASC sheets of a higher cellular density increased the expression levels of vascular endothelial growth factors and FGF2, whereas specific pro-inflammatory genes such as tumor necrosis factor-α and prostaglandin synthase 2 were downregulated 32 .…”
Section: Discussionmentioning
confidence: 98%